Kebersihan Tempat Tidur Dan Sprei Sebagai Faktor Risiko Keluhan Penyakit Kulit Di Wilayah Pesisir, Kampung Bugis, Kota Tanjungpinang Tahun 2018 - Hendra Dhermawan Sitanggang (POLTEKKES KEMENKES YOGYAKARTA, 2021)
Symptoms of skin disease were still a public health problem, globally and in Indonesia, especially in coastal areas in Tanjungpinang City. Several studies showed that personal hygiene and environmental sanitation as a risk factor for skin problems. The objective of this study was to determine the risk factors for symptoms of skin disease in RW 6, Kampung Bugis, which is a coastal area in Tanjungpinang in 2018. This study used cross-sectional design with 99 sample size and used purposive technique sampling. Data were collected by interviews and observation with a questionnaire and observation sheets. Data were analyzed with the chi-square test. The results revealed a relationship between hygiene beds and bed linen with symptoms of skin diseases (PR= 2.464 with 95% CI: 1.632 to 3.721). It means that the hygiene beds and bed linen were a risk factor for skin disease. The results also found that 92.9% of respondents had bad behavior towards the hygiene beds and bed linen. This behavior may be related to the condition of the living area which is a coastal area so that there is not enough space for them to dry the mattress. Therefore, people are advised to open windows regularly in the morning so that the mattress gets enough sunlight.